Differential effects of protein intake versus intake of a defined oligopeptide on FGF-21 in obese human subjects in vivo. Issue 2 (February 2021) - Fangmann, Daniela; Geisler, Corinna; Schlicht, Kristina; Hartmann, Katharina; Köpke, Jana; Tiede, Anika; Settgast, Ute; Türk, Kathrin; Schulte, Dominik M.; Altmann, Karina; Clawin-Rädecker, Ingrid; Lorenzen, Peter Ch; et al.
Summary: Background: FGF-21 is described as a powerful metabolic regulator with beneficial effects including glucose-lowering and improvement of insulin sensitivity without hypoglycaemia. On the other hand, FGF-21 is activated when muscle and other tissues are stressed by external effects or internal cellular pathogens that lead to shortcomings in metabolic balance. Previous results suggested that FGF-21 could be a promising target to develop future metabolic therapeutics. Purpose: The present study was performed to gain deeper insight into the regulation of FGF-21 by protein metabolism in obese human subjects. Methods: FGF-21 serum concentrations were measured in a cohort of n = 246 obese humans ± type 2 diabetes mellitus (T2DM) (median age 53.0 [46.0; 60.0] years and BMI 40.43 [35.11; 47.24] kg/m 2 ) and related to the nutritional protein intake. In addition, the effect of a novel oligopeptide purified from a β-casein hydrolysate on FGF-21 was examined in vitro in liver cells and in vivo in a human intervention study with the main focus on metabolic inflammation including 40 mainly obese subjects (mean age 41.08 ± 9.76 years, mean BMI 38.29 ± 9.4 kg/m 2 ) in a randomized 20 weeks double-blind cross-over design. Main findings: In the cohort analysis, FGF-21 serum concentrations were significant lower with higher protein intake in obese subjects without T2DM but not in obese subjects with T2DM. Furthermore, relative methionine intake was inversely related to FGF-21. While global protein intake in obesity was inversely associated with FGF-21, incubation of HepG2 cells with a β-casein oligopeptide increased FGF-21 expression in vitro. This stimulatory effect was also present in vivo, since in the clinical intervention study treatment of obese subjects with the β-casein oligopeptide for 8 weeks significantly increased FGF-21 serum levels from W0 = 23.86 pg/mL to W8 = 30.54 pg/mL (p < 0.001), while no increase was found for placebo. Conclusion: While the total nutritional protein intake is inversely associated with FGF-21 serum levels, a purified and well characterised oligopeptide is able to induce FGF-21 serum levels in humans. These findings suggest a differential role of various components of protein metabolism on FGF-21, rather than this factor being solely a sensor of total nutritional protein intake.